Przemysł paszowy w Polsce i determinanty jego rozwoju - Kapusta, Franciszek (Fodder Industry in Poland and Determinants of Its Development, 2007)
Intense animal production requires the use of condensed fodder in feeding animals, including high protein content mixed fodders. These mixes are provided by the fodder industry. Some amount of mixes is produced by fanners. In production of mixes the following ingredients are used: cereals, seeds of legume plants, meals (fish and bone), and leftovers of food industry, mainly pellet of oil plants, bran, pulpe, myolasse, and yeast. Poland is not producing enough components for mixed fodders and is forced to import them, especially pellet, bran, and seeds of legume plants. Production of high value fodders, especially mixes, is determined mainly by demand for animal products and necessity to intensify its production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 28-38